Introduction to the Special Issue on Qualitative Criminology and Victimology - Kokkalera, Stuti (Crime & delinquency, 2023)
Crime & Delinquency invited submissions for a special issue on Qualitative Criminology and Victimology in 2021. This double special issue aimed to amplify qualitative methodologies in criminology, criminal justice, and victimology research. The diverse range of articles and commentaries draw on a variety of qualitative methods to advance the discipline.